2003
DOI: 10.1093/jac/dkg103
|View full text |Cite
|
Sign up to set email alerts
|

Production of CTX-M-3 extended-spectrum beta-lactamase and IMP-1 metallo beta-lactamase by five Gram-negative bacilli: survey of clinical isolates from seven laboratories collected in 1998 and 2000, in the Kinki region of Japan

Abstract: The aim of this study was to research the distribution in the Kinki region of Japan of Enterobacteriaceae and Pseudomonas aeruginosa that produce extended-spectrum beta-lactamase (ESBL) and metallo beta-lactamase (MBL). One thousand isolates, 200 of each of four enterobacterial species (i.e. Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae and Serratia marcescens) and 200 of P. aeruginosa, were collected from seven different laboratories during two 2 month periods, one in 1998 and one in 2000. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 40 publications
3
44
1
Order By: Relevance
“…The rapid emergence of the CTX-Ms as the predominant ESBL type is not an isolated Lebanese phenomenon. A recent report on ESBL types in Enterobacteriaceae in Argentinean public hospitals found that CTX-Ms accounted for roughly 70% of all ESBLs found (31), with similar findings in studies conducted in Japan (35), China (23), the United Kingdom (22), and Spain (33). CTX-M-15 has already been identified in several countries, including Taiwan (36), Turkey (16), France (8), and United Kingdom (24).…”
Section: Discussionsupporting
confidence: 63%
“…The rapid emergence of the CTX-Ms as the predominant ESBL type is not an isolated Lebanese phenomenon. A recent report on ESBL types in Enterobacteriaceae in Argentinean public hospitals found that CTX-Ms accounted for roughly 70% of all ESBLs found (31), with similar findings in studies conducted in Japan (35), China (23), the United Kingdom (22), and Spain (33). CTX-M-15 has already been identified in several countries, including Taiwan (36), Turkey (16), France (8), and United Kingdom (24).…”
Section: Discussionsupporting
confidence: 63%
“…Several researchers have reported an incidence of metallo-␤-lactamase-producing P. aeruginosa of between 0.4 and 1.3% in Japan from 1992 to 2002 (5,7,14,16). In this study, we isolated 1.9% metallo-␤-lactamase-producing P. aeruginosa strains from geographically diverse regions in Japan.…”
mentioning
confidence: 67%
“…Among the clinically isolated P. aeruginosa, 1.7% in 1,058 isolates had metallo-β-lactamase genes with integron1, which could frequently form cassettes consisting of the genes of aminoglycoside modifying enzymes, or other β-lactamases resulting in several drug resistances (24). In a laboratory-based surveillance in Japan conducted during 1992-2002, metallo-β-lactamase-producing P. aeruginosa were identified at a rate of 0.4-1.9% (3,4,12,26). These results together with our observation suggest that the incidence of metallo-β-lactamase-positive P. aeruginosa has not increased in Japan.…”
Section: Discussionmentioning
confidence: 99%